Effect of an intensive 3-week preoperative home rehabilitation programme in patients with chronic obstructive pulmonary disease eligible for lung cancer surgery: a multicentre randomised controlled trial. Issue 11 (12th November 2017) - Laurent, Hélène; Galvaing, Géraud; Thivat, Emilie; Coudeyre, Emmanuel; Aubreton, Sylvie; Richard, Ruddy; Kwiatkowski, Fabrice; Costes, Frederic; Filaire, Marc
Abstract : Introduction: Surgery is the standard curative treatment for lung cancer but is only possible in patients with local tumour and preserved exercise capacity. Improving fitness before surgery can reduce postoperative complications and mortality. However, preoperative rehabilitation remains difficult to implement for several reasons. We aim to investigate the effectiveness of an intensive 3-week home-based preoperative exercise training programme on hospital discharge ability, postoperative complications and physical performance in patients with chronic obstructive pulmonary disease (COPD) who are eligible for lung cancer surgery. Methods and analysis: We designed a multicentre randomised controlled trial. The randomisation sequence will be generated and managed electronically by a research manager independent of assessments or interventions. We will recruit 90 patients with COPD and a diagnosis of lung cancer from four university hospitals. The rehabilitation group (R group) will receive a standardised preoperative home exercise programme for 3 weeks, combining both high-intensity training and usual physical therapy. The R group will perform 15 training sessions over 3 weeks on a cycloergometer. A physical therapist experienced in pulmonary rehabilitation will visit the patient at home and supervise one session a week. The R group will be compared with a control group receiving preoperative usual physical therapy only. The primary outcome will be hospital discharge ability assessed with a 10-item list. Secondary outcomes will be postoperative course (complication rate and mortality) as well as pulmonary function, exercise capacity and quality of life assessed 1 month before and the day before surgery. Ethics and dissemination: This protocol has been approved by the French health authority for research (2016-A00622-49) and the research ethics committee/institutional review board (AU1267). Adverse events that occur during the protocol will be reported to the principal investigator. The results will be published in an international peer-reviewed journal. Trial registration number: NCT03020251 .